Deficiency of Interleukin-1 Receptor Antagonist (DIRA): Report of the First Indian Patient and a Novel Deletion Affecting IL1RN - Mendonca, Leonardo O.; Malle, Louise; Donovan, Frank X.; Chandrasekharappa, Settara C.; Montealegre Sanchez, Gina A.; Garg, Megha; Tedgard, Ulf; Castells, Mariana; Saini, Shiv S.; Dutta, Sourabh; Goldbach-Mansky, Raphaela; Suri, Deepti; et al. (Journal of clinical immunology, 2017)
Purpose Deficiency of interleukin-1 receptor antagonist (DIRA) is a rare life-threatening autoinflammatory disease caused by autosomal recessive mutations in IL1RN. DIRA presents clinically with early onset generalized pustulosis, multifocal osteomyelitis, and elevation of acute phase reactants. We evaluated and treated an antibiotic-unresponsive patient with presumed DIRA with recombinant IL-1Ra (anakinra). The patient developed anaphylaxis to anakinra and was subsequently desensitized. Methods Genetic analysis of IL1RN was undertaken and treatment with anakinra was initiated. Results A 5-month-old Indian girl born to healthy non-consanguineous parents presented at the third week of life with irritability, sterile multifocal osteomyelitis including ribs and clavicles, a mild pustular rash, and elevated acute phase reactants. SNP array of the patient’s genomic DNA revealed a previously unrecognized homozygous deletion of approximately 22.5 Kb. PCR and Sanger sequencing of the borders of the deleted area allowed identification of the breakpoints of the deletion, thus confirming a homozygous 22,216 bp deletion that spans the first four exons of IL1RN . Due to a clinical suspicion of DIRA, anakinra was initiated which resulted in an anaphylactic reaction that triggered desensitization with subsequent marked and sustained clinical and laboratory improvement. Conclusion We report a novel DIRA-causing homozygous deletion affecting IL1RN in an Indian patient. The mutation likely is a founder mutation; the design of breakpoint-specific primers will enable genetic screening in Indian patients suspected of DIRA. The patient developed anaphylaxis to anakinra, was desensitized, and is in clinical remission on continued treatment.